New insights into the formation of volatile compounds in mainstream cigarette smoke - Liu, C. (Springer-Verlag, 2010)
A sampling system has been set up to monitor a group of volatile smoke analytes (nitric oxide, acetaldehyde, acetone, benzene, toluene, 1,3 butadiene, isoprene and carbon dioxide) from mainstream cigarette smoke on a puff-resolved basis. The system was able to record gas evolution profiles during puffing and interpuff periods without interruption (e.g. taking clearing puffs). Gas phase smoke analytes were sampled as close to the mouth end of the cigarette filter as possible in order to minimise any dead volume effect. The results revealed that, for some volatile species, a significant fraction (e.g. up to 30% for benzene) in the cigarette mainstream smoke had been generated during the preceding smoulder period. These species were trapped or absorbed within the cigarette rod and then subsequently eluted during the puff. The identification of the two sources of the mainstream smoke, a smouldering source and a puffing source, has not been reported before. The observation contributes to the fundamental knowledge of the cigarette smoke formation and may have implications on wider smoke chemistry and associated effects. [Figure: see text]